Los bifosfonatos y su relación a la inducción de la osteonecrosis maxilar en adultos. Revisión bibliográfica - Alverca Gaona, Nataly del Cisne (2021)
The bisphosphonates are drugs that are used to treat disease that affect to bone tissue. Nevertheless, it can cause complications like maxillary osteonecrosis characterized by exposure of necrotic bone tissue, that develops in patients who have received invasive dental treatmens that involve bone manipulation. In this bibliographic review thirty articles were considered analysing the existing relation between the bisphosphonates and the development of maxillary osteonecrosis, risk factores and treatment alternatives. The results obtained in this research indicate that this pathology mainly affects female patients due to its predisposition to develop osteoporosis, for which the administration of this drug is necessary. This research also showed that the intravenous route of administration is the one with the highest risk and that the drug with the greatest influence to develop maxillary osteonecrosis is zoledronate. Demonstrating that the mandibular bone is the most affected with the administration of these drugs. Key words: Maxillary osteonecrosis, bisphosphonates, jawbone, bone resorption.